Counseling and Psychotherapy with Couples and Families - Maulida Fitri; Yeni Karneli; Mudjiran (Journal Of Psychology, Counseling And Education, 2024)
The aim of this research is to study counseling and psychotherapy in dealing with problems of couples, children, teenagers and families. To achieve this goal, this research uses literature research or literature review methods. This research collects literature from various books and articles related to the subject discussed with the keywords family counseling and psychotherapy. The research results show that the basic problems in counseling and psychotherapy with children, adolescents, couples and families are being able to achieve accurate communication, handle feelings of dependency, collaborate with the whole family, and help clients realize their need for help. For children, the main goal of counseling and psychotherapy in the form of individual and group therapy is to help them achieve a strong ego so that they can overcome environmental demands and their own inner stress.